Hyperuricaemia and development of type 2 diabetes mellitus in Asian population. (4th February 2018) - Choi, Byoung Geol; Kim, Dae Jin; Baek, Man Jong; Ryu, Yang gi; Kim, Suhng Wook; Lee, Min Woo; Park, Ji Young; Noh, Yung‐Kyun; Choi, Se Yeon; Byun, Jae Kyeong; Shim, Min Suk; Mashaly, Ahmed; et al.
Summary: Recently, meta‐analysis studies reported that hyperuricaemia is associated with higher incidence of type 2 diabetes mellitus (T2DM), however, there are limited data on the Asian population. The aim of this observational study is to estimate the long‐term impact of hyperuricaemia on the new‐onset T2DM and cardiovascular events. This study is based on a single‐centre, all‐comers, and large retrospective cohort. Subjects that visited from January 2004 to February 2014 were enrolled using the electronic database of Korea University Guro Hospital. A total of 10 505 patients without a history of T2DM were analyzed for uric acid, fasting glucose and haemoglobin (Hb) A1c level. Inclusion criteria included both Hb A1c <5.7% and fasting glucose level <100 mg/dL without T2DM. Hyperuricaemia was defined as a uric acid level ≥7.0 mg/dL in men, and ≥6.5 mg/dL in women. To adjust baseline confounders, a propensity score matching (PSM) analysis was performed. The impact of hyperuricaemia on the new‐onset T2DM and cardiovascular events were compared with the non‐hyperuricaemia during the 5‐year clinical follow‐up. After PSM, baseline characteristics of both groups were balanced. In a 5‐year follow‐up, the hyperuricaemia itself was a strong independent predictor of the incidence of new‐onset T2DM (HR, 1.78; 95% CI, 1.12 to 2.8). Hyperuricaemia was a strong independent predictor of new‐onset T2DM, which suggests a substantial implication for a correlation between uric acid concentration and insulin resistance (or insulin sensitivity). Also, hyperuricaemia is substantially implicated in cardiovascular risks and the further long‐term cardiovascular events in the crude population, but it is not an independent predictor of long‐term cardiovascular mortality in the matched population.